Penerapan Teams Games Tournament Bermedia Couple Card untuk Meningkatkan Berpikir Kritis dan Hasil Belajar Siswa - Puspitasari, Ai Nina Karlina; Nuraeni, Ani; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2019)
The purpose of this study is to train students critical thinking and to improve student learning outcomes by using the Teams Games Tournament model with Couple Card media. The subject used is VB class students SDN Pasanggrahan 1 VB class. In this study the indicators taken from critical thinking are analyzing so that students are expected to be able to analyze social studies subjects about material social interaction. The method used in this study is a class action research method. Data obtained from the research results from the activities of Teams Games Tournament in groups, evaluation tests, observations, interviews, and field notes. Student learning outcomes in the initial data by 27% increased to 95%. Then the results of group critical thinking in the first cycle of 27% increased to 77%. And the results of critical thinking of individual students in the first cycle of 50% increased to 77%. So that the results of these studies prove that the application of the Teams Games Tournament model with Couple Card is able to improve critical thinking and student learning outcomes.